2007
DOI: 10.1542/peds.2007-1041
|View full text |Cite
|
Sign up to set email alerts
|

Does Cerebellar Injury in Premature Infants Contribute to the High Prevalence of Long-term Cognitive, Learning, and Behavioral Disability in Survivors?

Abstract: Cerebellar hemorrhagic injury in preterm infants is associated with a high prevalence of long-term pervasive neurodevelopment disabilities and may play an important and underrecognized role in the cognitive, learning, and behavioral dysfunction known to affect survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
386
4
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(407 citation statements)
references
References 45 publications
(65 reference statements)
14
386
4
3
Order By: Relevance
“…Retrospective studies have suggested an association between LBW and/or preterm birth and risk for ASD. [4][5][6][7][8][9][10] Prospective studies in children [11][12][13] and adolescents 3,[14][15][16] have supported this suggestion. Most prospective studies, however, have determined risk for ASD on the basis of screening instruments rather than a definitive diagnosis.…”
mentioning
confidence: 91%
“…Retrospective studies have suggested an association between LBW and/or preterm birth and risk for ASD. [4][5][6][7][8][9][10] Prospective studies in children [11][12][13] and adolescents 3,[14][15][16] have supported this suggestion. Most prospective studies, however, have determined risk for ASD on the basis of screening instruments rather than a definitive diagnosis.…”
mentioning
confidence: 91%
“…Clinical, epidemiological and experimental studies have revealed that key factors, such as inflammation and oxidative stress contribute considerably to white-and grey-matter injury in premature infants, whose brains are particularly susceptible to damage (Kaindl et al, 2009). In infants surviving premature birth, cerebellar hemorrhagic injury is also associated with a high prevalence of neurodevelopmental disabilities (Limperopoulos et al, 2007). The resulting long-term neurologic complications may include learning difficulties, behavioral and socio-emotional concerns, and poor general health outcomes.…”
Section: The Role Of Prematuritymentioning
confidence: 99%
“…For instance, Johnsen et al 3 found cerebellar injury on brain magnetic resonance images (MRIs) in 64% of children who were born with extremely low birth weight and who had cerebral palsy (CP). In addition, Limperopoulos and colleagues 4 reported higher rates of mortality, and motor and non-motor disabilities in preterm infants who developed isolated CH. In our unit, the increased survival of extremely preterm infants over time was associated with a parallel decrease in CP and motor impairment rates, yet no similar decline in mental impairment was observed.…”
Section: Introductionmentioning
confidence: 98%